Analisis Konfigurasi Jaringan Jalan dengan Metode Space Syntax sebagai Strategi Mitigasi Kriminalitas - Muadzin, Kevin Fadillah (COMPACT: Spatial Development Journal, 2023)
The increasing criminal cases in Indonesia call for innovative solutions. Evolution in technology and easy access to spatial data highlight the potential of urban analytics as a problem-solving tool. One of the method within urban analytics is the space syntax approach. Space syntax is a spatial analysis technique used to study the relationship between the configuration of street networks and human movement patterns within them. Several studies have explored significant correlations between street network configurations and crime rates. This paper discusses and identifies characteristics in the configuration of street networks associated with crime rates using the space syntax method. It is followed by the application of the principles of Crime Prevention Through Environmental Design (CPTED) to these street segment characteristics. The integration of space syntax as a method for predicting crime rates and CPTED as a method for prevention holds potential as a crime prevention strategy.